Effects of Speech Rate and Practice on the Allocation of Visual Attention in Multiple Object Naming - Meyer, Antje; Wheeldon, Linda R.; Konopka, Agnieszka (Frontiers in Psychology, 2012)
Earlier studies had shown that speakers naming several objects typically look at each object until they have retrieved the phonological form of its name and therefore look longer at objects with long names than at objects with shorter names. We examined whether this tight eye-to-speech coordination was maintained at different speech rates and after increasing amounts of practice. Participants named the same set of objects with monosyllabic or disyllabic names on up to 20 successive trials. In Experiment 1, they spoke as fast as they could, whereas in Experiment 2 they had to maintain a fixed moderate or faster speech rate. In both experiments, the durations of the gazes to the objects decreased with increasing speech rate, indicating that at higher speech rates, the speakers spent less time planning the object names. The eye-speech lag (the time interval between the shift of gaze away from an object and the onset of its name) was independent of the speech rate but became shorter with increasing practice. Consistent word length effects on the durations of the gazes to the objects and the eye speech lags were only found in Experiment 2. The results indicate that shifts of eye gaze are often linked to the completion of phonological encoding, but that speakers can deviate from this default coordination of eye gaze and speech, for instance when the descriptive task is easy and they aim to speak fast.